A case of unresectable combined hepatocellular and cholangiocarcinoma treated with atezolizumab plus bevacizumab. Issue 7 (25th July 2022) - Saito, Naoto; Hatanaka, Takeshi; Nakano, Sachi; Hazama, Yoichi; Yoshida, Sachiko; Hachisu, Yoko; Tanaka, Yoshiki; Yoshinaga, Teruo; Kashiwabara, Kenji; Kubo, Norio; Hosouchi, Yasuo; Tojima, Hiroki; et al.
Abstract: An 81‐year‐old man initially underwent right hepatic lobectomy for liver cancer and was pathologically diagnosed with combined hepatocellular and cholangiocarcinoma (CHC). At 13 months after resection, multiple lymph node metastases were observed. We started atezolizumab plus bevacizumab (Atez/Bev), achieving a 7.5‐month progression‐free survival. Atez/Bev might exhibit efficacy for CHC patients. Abstract : Although no standard systemic chemotherapy for combined hepatocellular and cholangiocarcinoma patients has yet been established, atezolizumab plus bevacizumab, which is a combination therapy of anti‐programmed death ligand‐1 and anti‐vascular endothelial growth factor, might exhibit good therapeutic outcome.